STABILISASI TANAH LEMPUNG DENGAN PENAMBAHAN SERABUT KELAPA PADA PENGUJIAN KUAT GESER LANGSUNG (DIRECT SHEAR TEST) - Galih Yuda Setiawan; M. Ikhwan Yani; Okrobianus Hendri (INFO-TEKNIK, 2021)
Clay is ground that has some properties bad that can interfere with the strength of a building construction so that the construction that can experience damage physically are not able to be predicted. Bad Character by soil clay are relatively large, high plasticity, and strong low shear value. With the development of soil mechanics, various soil improvement methods can be used to solve this situation. An alternative that can be used as a soil stabilizer is coconut fiber. Selection of coconut fibers as mixed material because coconut fibers can add strong sliding soil, material that is easy to pass water. The purpose of this study is to determine the effect of adding coconut fiber on the value of clay stabilizers.. The research method used is field survey and sempel retrieval method is with laboratory analysis approach, where strong shear testing is carried out three times with variations of coconut fiber as much as 0.5%, 1% and 1.5% with coconut fiber length of 3 cm and 5 cm. From the test results the largest increase in the addition of coconut fiber with a percentage of 1.5% of the length of coconut fibers 3 cm and 5 cm in clay increased the angle of shear of the soil (ø) by 170 and 280, cohesion (c) of 0.2387 kg/cm2 and 0.2383 kg/cm2, shear strength (τ) of 0.281 kg/cm2 and 0.312 kg/cm2, or it can be said that the addition of 1.5% coconut fiber will increase the strong value of shear by 47.3% and 63.46%.